Analysis of Firm Value, Financial Policy and Financial Flexibility: The Case of Companies Listed on the Stock Exchange of Thailand - Hermkhunthod, Ochin; Petchchedchoo, Pattanant; Kumsuprom, Siridech; Panmanee, Panarat (Rajapark Journal, 2024)
This research aims to study and synthesize the effect of financial policy on financial flexibility, the effect of financial flexibility on firm values, and the effect of financial policy on firm values through financial flexibility. This research is quantitative. The selection of the sample is a purposive sampling by selecting only companies listed in the SET100 index between 2020 and 2022, excluding companies with incomplete data and companies in the financial industry group. Structural equation modeling (SEM) was used to analyze the data in the research. The research found that financial policy related to dividend payment had a positive association with financial flexibility, while cash holding and capital structure did not affect financial flexibility. Moreover, financial flexibility also did not affect firm value. Lastly, financial policy related to cash holding, capital structure, and dividend payment did not have an indirect effect on firm values through financial flexibility. This is because the debt level of the company is high; although the company can access capital sources, the company should not have more financing to maintain the financial stability of the company.